Bovine tuberculosis: Diagnosis by PCR technique in bovine milk samples: Al-Rubiaii E.M.; Alwan M.J. and Al- Thwani A. N. - Alwan, Mohammed J. (The Iraqi Journal of Veterinary Medicine, 2013)
The aim of this study was to determine the percentage of borne tuberculin infection in milk sample by using PCR. (102) milk samples were collected from cows , AL-Dejella (39) samples, AL-Suara (20) samples cow station, AL-Fthalia (20) samples, AL-Azezia (11) samples and AL-Twarege (12) samples (Iraq) during the period July 10th 2010 to Nov.30th 2010. The samples were examined by direct smear stained by Ziehle-Neelson stain, culture methods and confirmed the isolates by Polymerase Chain Reaction (PCR) assay. The results showed that 5, 102 (4.9%) milk samples were M. bovis positive that were detected by direct milk smear method and 10 out 102(9.8%) M.bovis +ve were detected by culture method and PCR assay. The results also showed that high percentage of bacterial isolates from milk samples AL-Dejella city show (12.8%) by culturing and PCR method followed by AL-Suara (10%), AL-Fthelia (10%), Al-Twarege (8.3%) but no bacterial isolation was recorded in AL-Azezia milk samples. This study concluded that M.bovis infection was spreading in dairy cow within the mentioned areas and PCR was more sensitive, rapid, and accurate technique for M.bovis infection diagnosis.